Sustainability perceptions in tourism and hospitality: A mixed-method bibliometric approach - Santos, Luís Lima (2020)
In the post-Covid-19 era, tourism impacts and the role played by sustainable planning on the long-term success of destinations have gained renewed importance. Understanding the image and perceptions tourists hold of a destination is vital for tourism planning, as they play a key role in tourists’ decisions. Considering the importance of these two key concepts (perceptions and sustainability), the present paper contributes to the advancement of knowledge on sustainable tourism by characterizing the state of the art of Sustainability Perceptions in Tourism and Hospitality (SPTH). To this end, the scientific literature on the topic was mapped through a combination of three bibliometric analysis techniques, namely: evaluative, relational, and systematic bibliometric analysis. These were based on productivity and impact indicators, including SciVal topic prominence. The results reveal that sustainability perceptions in SPTH focus on tourists’, stakeholders’, and residents’ perceptions. These findings highlight the need for involving local communities in the destination planning process to align the outcomes of tourism development with their expectations. Finally, this paper presents an original methodological contribution, as it is the first to apply the SciVal topic prominence analysis to SPTH.